Analisis Muatan Literasi Budaya dan Kewargaan Pada Buku Siswa Tema 1 Kelas IV Sekolah Dasar - Sinwani Sinwani; Dessy Setyowati; Yunika Afryaningsih (Edukhasi: Jurnal Inovasi Pendidikan, 2023)
The purpose of this study was to find out the contents of cultural literacy and citizenship in the Student's book Theme 1 The Beauty of Togetherness in Elementary Schools. The research method used in this study is a qualitative research method. Research on the theme 1 student book shows that cultural aspects as a natural way of thinking through language and behavior are not included in the theme 1 student book. Aspects of Art as a Cultural Product are included in the theme 1 student book and have provided space for students to add insight and skills The aspects of Multicultural Citizenship and Participation are the aspects that appear the most in Theme 1 student books. The aspect of nationalism is included in the student book on theme 1. This can be seen from awareness in public relations as citizens The inclusiveness aspect is contained in the theme 1 student book, this can be seen from the indicators of building tolerance and respect for culture. Aspect Direct Experience in the theme 1 student book is included, this can be seen in the student activities contained in the student book theme 1 the beauty of togetherness.